Social Security 1935 - Rosenthal, Jean W., 1945- (SAGE Knowledge. Cases., 2016)
On August 14, 1935, two years and five months after his Inauguration in March 1933, Franklin Delano Roosevelt signed Public Law 271, the Social Security Act. Although the idea of providing benefits for the aged was not new, the impetus and urgency for creating Social Security and other New Deal welfare programs had come from Frances Perkins, Roosevelt's Secretary of Labor. With critics arguing that the system went too far and others arguing that the new program did not go far enough, Perkins designed the Social Security Act to fit both economic and political realities of the time. Nearly a century later, observers continue to wonder whether Perkins made the right choices.